Cu-catalyzed sequential C-N bond formations: expeditious synthesis of tetracyclic indoloindol-3-ones - Kulkarni, Anand M.; Srinivas, Kolluru; Deshpande, Mukund V.; Ramana, Chepuri V. (Organic Chemistry Frontiers, 2016)
The tetracyclic indoloindol-3-one core has been forged from easily accessible 2,2'-bis-bromochalcones employing a reaction cascade comprising Cu-catalyzed SNAr with azide; nitrene C-H insertion and intramolecular Ullmann reaction with all three C-N bond formations in one-go.